TINJAUAN KEAMANAN DAN KESELAMATAN TERHADAP PENUMPANG KAPAL WISATA SUNGAI KAPUAS (STUDI DI WATERFRONT CITY PONTIANAK) - I D R I S NIM. A1011191280 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractPontianak City is the capital of West Kalimantan Province, which is geographically passed by the Equator and the Kapuas River, which is used as a tourism sector, such as Waterfront City and Kapuas River Tour Boats. Problems that are often encountered on the Kapuas River Tour Ship include no tickets and passenger data collection. Then there is no easily accessible safety equipment such as Life Jackets or life jackets, Life Bouys or life jackets, Fire bottles or Fire Extinguishers (APAR) and Equipment first aid The research aims to obtain data and information and then analyze the implementation and factors that have not implemented security and safety standards for Kapuas River Tour Boats, security and safety standards by business actors on Kapuas River Tour Boats, and forms of government supervision of the operation of Kapuas River Tour Boats in Pontianak Waterfront City. The legal research method is empirical and analytical descriptive in nature, by describing the situation as it was that had occurred at the time the research was carried out or by disclosing all the problems based on real facts, then classifying legal data and material, examining it qualitatively. The implementation of security and safety standards by Kapuas River Tourism Ship business actors has not been fully implemented. It is proven that ship owners do not pay attention to the security and safety of ships as determined by statutory regulations. The cause of not implementing security and safety standards consists of internal factors, namely the awareness of the organizers and external factors from the government. Government oversight of the operation of the Kapuas River Tour Boat in Pontianak Waterfront City with direct supervision and indirect supervision, as well as the government controlling the inappropriate vessels.Keywords : Passengers, Security and Safety, Kapuas River Tour Ship Abstrak Kota Pontianak adalah ibukota Provinsi Kalimantan Barat, yang secara geografis di lewati garis Khatusltiwa dan Sungai Kapuas yang dimanfaatkan sebagai sektor pariwisata seperti Waterfront City dan Kapal Wisata Sungai Kapuas. Permasalahan yang sering ditemui di Kapal Wisata Sungai Kapuas diantaranya tidak ada karcis, pendataan penumpang, kemudian tidak tersedia alat keselamatan yang mudah dijangkau seperti Life Jacket atau baju pelampung, Life Bouy atau pelampung, Botol api atau Alat pemadam api (APAR) dan Alat-alat P3K. Penelitian bertujuan untuk memperoleh data dan informasi kemudian menganalisis pelaksanaan dan faktor belum dilaksanakannya standar keamanan dan keselamatan Kapal Wisata Sungai Kapuas standar keamanan dan keselamatan oleh pelaku usaha Kapal Wisata Sungai Kapuas, dan bentuk pengawasan Pemerintah terhadap beroperasinya Kapal Wisata Sungai Kapuas di Waterfront City Pontianak. Metode penelitian hukum empiris dan bersifat deskriptif analisis, dengan menggambarkan keadaan sebagaimana adanya yang telah terjadi pada saat penelitian itu dilaksanakan atau dengan mengungkapkan segala permasalahanya berdasarkan fakta nyata, kemudian mengklasifikasi data dan bahan hukum, mengkaji secara kualitatif. Pelaksanaan standar keamanan dan keselamatan oleh pelaku usaha Kapal Wisata Sungai Kapuas belum dilaksanakan sepenuhnya terbukti para pemilik kapal tidak mengindahkan keamanan dan keselamatan kapal sebagaimana dtitentukan oleh aturan perundang-undangan. Penyebab belum dilaksanakannya standar keamanan dan keselamatan, terdiri dari faktor internal yaitu kesadaran penyelenggara dan faktor eksternal dari pihak pemerintah. Pengawasan Pemerintah terhadap beroperasinya Kapal Wisata Sungai Kapuas di Waterfront City Pontianak dengan pengawasan langsung dan pengawasan tidak langsung, serta pemerintah melakukan penertiban kepada kapal yang tidak sesuai.Kata Kunci : Penumpang, Keamanan dan Keselamatan, Kapal Wisata Sungai Kapuas